Alih Aksara dan Alih Bahasa Manuskrip Inilah Sejarah Ringkas Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Pengembang Agama Islam di Aceh Ditulis oleh Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang - Ahdi, Wafiatul; Hasanuddin WS, Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2024)
This article aims to: (a) present a description of the manuscript A Brief History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) the Developer of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang, (b) present a transliteration of the text A Brief History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Developers of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang, (c) presents a translation of the text A Brief History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Developers of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang. This research is included in the type of philological research. The object of this research is the manuscript A Brief History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) the Developer of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang. This research method is a philological research method based on several research stages, namely the data collection stage using the library study method, the data processing stage using the descriptive method, the transliteration stage uses the transliteration method, then the translation stage uses the translation method. There are three results of this research, namely: (1) description of the manuscript A Brief History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Developer of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang, which consists of 18 aspects, (2) transliteration of the text A Concise History of Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Developer of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang presented from Arabic-Malay script into Latin script, (3) presentation of the translation of the text Concise History Auliyaullahushshalihin Syekh Abdurrauf (Syekh Kuala) Developer of the Islamic Religion in Aceh written by Imam Maulana Abdul Manaf Amin Batang Kabung Kota Tengah Tabing Padang from Malay and some Minangkabau vocabulary into Indonesian.